Bitwise method for the binary-coded operands conversion based on mathematical logic - Lukashenko, Andriy; Harder, Dmytro; Lukashenko, Volodymyr; Fedorov, Evgenyi; Lukashenko, Valentyna; Utkina, Tetyana; Mitsenko, Serhii; Rudakov, Kostiantyn (Eastern-European Journal of Enterprise Technologies, 2018)
This paper addresses the development and examination of the unconventional highly-efficient bitwise tuple-tabular logical-reverse method, underlying the construction of precision models of computational information converters, represented in the form of unipolar binary-coded operands with a positionally-ordered notation. Modern models of converters, built using traditional methods, are typically not computationally loaded and are the aligning components that ensure the required form of information representation both at the input and output of the computing device. At the same time, they have a number of constraints that require hardware support, which leads to an increase in the weight and dimensions, compromises reliability and energy-time indicators, and increases the cost. Therefore, development of the new unconventional method that converts various types of positionally-ordered binary-coded operands into certain values for a code combination and vice versa, using the same tabular compliance data (previously calculated) is a relevant task. The method implies the construction of compliance tables based on formal logic; determining the values for corrective constants using the ХОR operation; the elimination of information redundancy owing to the tuple decomposition and the synthesis of components for the model of a computational converter of information. The totality of procedures ensures the versatility, high performance speed and reliability, reduces energy consumption while maintaining the precision of results. Verification of the proposed logical-mathematical model for constructing an effective method that converts various types of binary-coded operands has been confirmed by calculating the corrective constants given in tables, as well as during an experiment. The experiment was conducted on the designed physical model with a single numeric memory unit that converts a binary code into the Gray code and vice versa. The proposed original multifunctional computational converters make it possible, at lower energy-time and hardware costs, to solve local control tasks in the computer-integrated systems for special purposes in order to manage high-speed technological processes or handle autonomous physical objects